Recreational use of public waterways and the impact of water quality - Benjamin Breen; John A. Curtis; Stephen Hynes (The Economic and Social Research Institute (ESRI), 2017)
This study combines routinely collected water quality data from Ireland and an on-site survey of waterway users to evaluate how water quality affects trip days demanded for recreational activities. Water quality measures employed in the analysis include Water Framework Directive (WFD) ecological status as well as several physio-chemical measures. The analysis finds some evidence that higher levels of recreational demand occur at sites with the highest quality metric measures. However, in many of the estimated models there is no statistical association between the water quality metric (e.g. WFD status, BOD, ammonia, etc.) and the duration of the recreational trip. As most sites considered in the analysis have relatively high levels of water quality this result possibly suggests that above an unspecified threshold level that water quality is not a significant determinant of recreational trip duration. Model estimates also reveal a relatively high valuation among participants for water-based recreational activity with an estimate of mean willingness to pay equivalent to exteuro204/day.
Keywords: 330